2022
DOI: 10.48550/arxiv.2207.03515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermal spin dynamics of Kitaev magnets -- scattering continua and magnetic field induced phases within a stochastic semiclassical approach

Abstract: The honeycomb magnet α−RuCl3 is a prime candidate material for realizing the Kitaev quantum spin liquid (QSL), but it shows long-range magnetic order at low temperature. Nevertheless, its broad inelastic neutron scattering (INS) response at finite frequency has been interpreted as that of a 'proximate QSL'. A moderate in-plane magnetic field indeed melts the residual zigzag order, giving rise to peculiar intermediate field phases before the high-field polarized state. In INS measurements the low-frequency spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…for T > ∼ T N ). However, recent work [40] has demonstrated that electrons scattering off the fluctuations of a "cooperative" paramagnet [41][42][43][44][45][46][47][48] can not account for a T −linear resistivity; instead the resistivity saturates to a temperature-independent value for T T N . Starting with a microscopic model, we will now demonstrate that the resolution to the conundrum lies in a previously ignored and non-trivial interaction term between the Pd-electrons, the Cr-spins, and phonons, as encoded in an electron-magneto-elastic (EME) coupling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…for T > ∼ T N ). However, recent work [40] has demonstrated that electrons scattering off the fluctuations of a "cooperative" paramagnet [41][42][43][44][45][46][47][48] can not account for a T −linear resistivity; instead the resistivity saturates to a temperature-independent value for T T N . Starting with a microscopic model, we will now demonstrate that the resolution to the conundrum lies in a previously ignored and non-trivial interaction term between the Pd-electrons, the Cr-spins, and phonons, as encoded in an electron-magneto-elastic (EME) coupling.…”
mentioning
confidence: 99%
“…In recent work [40], some of us analyzed the properties of a subset of the terms, (H el + H S + H K ), in Eq. (1a) at leading order in a small J K by approximating the local-moments as O(3) vectors, but capturing their complex precessional dynamics using the Landau-Lifshitz equations [41][42][43][44][45][46][47][48]. While this leads to an interesting frequency dependence and momentum-dependent crossovers in the electronic self-energy, the temperature dependence can be understood entirely based on a hightemperature expansion with uncorrelated local-moments.…”
mentioning
confidence: 99%
“…We note at the outset that in the temperature window of interest and for a "weak" Kondo-coupling, the intrinsic quantum mechanical Kondo-physics associated with the quenching of the local moment will be irrelevant. The dynamics of frustrated magnets in their cooperative paramagnetic phase tends to be well-described by the classical Landau-Lifshitz equations of motion governed by H S , even for small spin lengths S far from the classical limit S → ∞ [22][23][24][25][26][27][28][29]:…”
mentioning
confidence: 99%